Hepatic and splanchnic nitric oxide activity in patients with cirrhosis. Issue 5 (1st May 1999) - Sarela, A I; Mihaimeed, F M A; Batten, J J; Davidson, B R; Mathie, R T
Abstract : BACKGROUND: In animal models of cirrhosis, altered activity of nitric oxide (NO) has been implicated in the pathogenesis of increased intrahepatic portal vascular resistance and abnormal mesenteric vasodilatation. AIMS: To investigate NO activity in the liver and splanchnic vascular bed of patients with cirrhosis. METHODS: Activity of the calcium dependent constitutive and calcium independent inducible isoforms of NO synthase (cNOS and iNOS, respectively) was assayed biochemically in biopsy specimens of liver and a vascular portion of the greater omentum (representative of mesenteric vasculature) obtained from patients with cirrhosis undergoing liver transplantation (n=14) and non-cirrhotic control patients undergoing liver resection for metastases (n=9). The concentration of NO metabolites (NO2 + NO3 ) in portal and peripheral venous plasma was measured. RESULTS: The activity of cNOS was lower in cirrhotic compared with non-cirrhotic subjects for both liver and omentum. Hepatic and omental iNOS activities did not differ significantly between the two groups. Portal (NO2 + NO3 ) was threefold higher in cirrhotic than non-cirrhotic patients, but no differences were observed in systemic venous samples from the two groups. CONCLUSIONS: The activity of cNOS is diminished in the cirrhotic human liver. The resultant decrease in constitutive NO release may promote an increase in the intrahepatic portal vascular resistance. Elevated portal venous (NO2 + NO3 ) indicates enhanced splanchnic vascular release of NO in cirrhotic patients, but the absence of increased NOS activity in the mesenteric vasculature suggests differential regulation of NO synthesis within the splanchnic vascular bed.